HUBUNGAN ASUPAN ENERGI PROTEIN DAN FREKUENSI OLAHRAGA DENGAN DAYA TAHAN KARDIORESPIRASI DAN MASSA OTOT PADA MAHASISWA IPB - Putra, Rangga Nuansa; Amalia, Leily (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to analyze the relationship between energy-protein intake and exercise frequency with cardiorespiratory endurance and muscle mass. The study was conducted between October 2013 and February 2014 at campus of Bogor Agricultural University. Design of the study was cross sectional.Subjects were 25 students of football UKM and 25 students of non-UKM groups. In average, nutritional status of subjects was normal. Intakes and adequacy level of energy, protein, fat, and carbohydrate of subjects in UKM group were significantly higher than intakes of non-UKM group. Exercise frequency of subjects in UKM group was more frequent (4.04 times/week) than that of non-UKM group (1.24 times/week). Cardiorespiratory endurance of UKM group (40.1 ml O2/kg BW/minute) was significantly higher than of non-UKM group (36.2 ml O2/kg BW/minute). However, the muscle mass of subjects was not significantly different, namely 28.3 kg in UKM group and 28.4 kg in non-UKM group. There was a significant relationship between cardiorespiratory endurance and energy intake(p=0.003, r=0.415), protein intake (p=0.009, r=0.365), and exercise frequency (p=0.004, r=0.395); but there was no significant relationship between muscle mass and exercise frequency, energy nor protein intake (p>0.05).